Fundamental dimensions of personality underlying spirituality: Further evidence for the construct validity of the RiTE measure of spirituality. (March 2015) - Chang, Edward C.; Jilani, Zunaira; Yu, Tina; Fowler, Erin E.; Lin, Jiachen; Webb, Jon R.; Hirsch, Jameson K.
Highlights: Examined the construct validity of the RiTE measure of spirituality against the NEO-FFI. Analyses indicated different associations for the three RiTE spirituality dimensions. NEO-FFI clusters accounted for large amounts of variance in spirituality dimensions. The RiTE appears to be a promising multidimensional measure of spirituality. Abstract: This study examined the construct validity of the RiTE as a multidimensional measure of spirituality in relation to the five-factor model of personality in a sample of 325 college students. Results of correlational and regression analyses provided support for the notion that the dimensions of ritualistic, theistic, and existential spirituality tapped by the RiTE, are empirically distinguishable. Overall, our findings provide further evidence for the construct validity of the RiTE and for the potential value of measuring spirituality as a multidimensional phenomenon in the study of religious processes.